Antecedentes familiares e intolerancia a la lactosa en los niños del 2do Año de Básica de la Escuela Lauro Damerval Ayora # 1 de la ciudad de Loja en el periodo noviembre 2012 - mayo 2013 - Aguilar Analuisa, Danny Israel (2014)
Lactose intolerance is the inability to digest significant amounts of carbohydrate milk. The thesis put forth is going to take another point of view in the administration of milk and its derivatives, as some children were suffering from lactose intolerance symptomatic and non-symptomatic and there isn’t an early detection, but would be associated with different gastrointestinal pathologies very unrealistic. Through this investigation seeks to determine the direct relationship between Family History and Lactose intolerance in children 2nd Year Basic Education School “Lauro Damerval Ayora” # 1 in the city of Loja in the period November 2012 – May 2013. This gives the importance of early detection of this disease that directly affects growth and development in children. Using for this investigation Quantitative Method, case-control Analytical, Descriptive, transversal study, and technicians: Clinical test for lactose intolerance, and Instrument: test of tolerance of lactose in pH of dregs in 70 children. After analyzing the data obtained from the survey and test clinical lactose tolerance in children (as), it was determined that there is a direct relationship between family history and the probability about that the disease is present in their childrenas, it was concluded that of all children who have a family history of lactose intolerance in 70% of infants there is also this condition, after making a diagnosis suggestive through Tolerance Test lactose in pH of dregs. Keywords: Family History, Intolerance, Lactose.